2021
DOI: 10.3390/plants10102079
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Inoculation of Phosphorus-Solubilizing Bacteria and Phosphorus as Sustainable Fertilizer on Yield and Quality of Mung Bean (Vigna radiata L.)

Abstract: Globally, the availability of phosphorus (P) to crops remains limited in two-thirds of the soils, which makes it less accessible to plants and ultimately associated with low crop yields. The present study investigated the effect of phosphorus-solubilizing bacteria (PSB; Pseudomonas spp.) for the improvement of phosphorus in mung bean (Vigna radiata) varieties and growth of net grain and biological yields. Results showed that inoculation of mung bean varieties with PSB at the rate of 100 g/kg seed significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Phosphorus is important for nodule development in legume crops [11]. P has been reported to increase the yield components and grain yield of mung bean [15][16][17]. The low N in rainfed sandy soils [9] may also limit mung bean performance.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus is important for nodule development in legume crops [11]. P has been reported to increase the yield components and grain yield of mung bean [15][16][17]. The low N in rainfed sandy soils [9] may also limit mung bean performance.…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that mung bean inoculated with PSB ( Pseudomonas spp.) could increase root length and dry weight 46 . Our study also confirmed that the root morphological parameters of the treatment inoculated with T. viride were better than those without inoculation (Table 3 ).…”
Section: Discussionmentioning
confidence: 98%
“…Bilal et al [ 121 ] investigated the effect of Pseudomonas spp., a PSB, as inoculant for mung bean varieties, and reveal a significant improvement in grain yield of 882.23 kg ha −1 , similar to 70 kg ha −1 of P fertilization, greater than the control. Other parameters such as root and shoot dry weight, root and shoot length, weight of 1000 grains, and harvest index also improve with Pseudomonas inoculation.…”
Section: Pgpr Benefits: Nutrition Enhancement and Tolerance To Abioti...mentioning
confidence: 99%